2022
DOI: 10.3389/fimmu.2022.859668
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Immune Modulatory Characteristics of Bone Marrow Mesenchymal Stromal Cells in Patients With Aplastic Anemia: A Systematic Review

Abstract: BackgroundIn most patients with aplastic anemia (AA), the diagnosis is limited to a description of the symptoms. Lack of understanding of the underlying pathophysiological mechanisms causing bone marrow failure (BMF), hampers tailored treatment. In these patients, auto-immune cell-mediated destruction of the bone marrow is often presumed to be the causative mechanism. The status of the bone marrow microenvironment, particularly the mesenchymal stromal cell (MSC) component, was recently suggested as a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Using their basic properties as indicators, we firstly documented lower potential of proliferation and differentiation in SAA MSCs without changes in their morphologies and surface marker expressions [ 8 ]. Since then, these characteristics of SAA MSCs have been investigated in a number of studies [ 18 ]. The majority indicated worse proliferative ability of SAA MSCs, and all studies demonstrated no difference in their surface marker expression.…”
Section: Discussionmentioning
confidence: 99%
“…Using their basic properties as indicators, we firstly documented lower potential of proliferation and differentiation in SAA MSCs without changes in their morphologies and surface marker expressions [ 8 ]. Since then, these characteristics of SAA MSCs have been investigated in a number of studies [ 18 ]. The majority indicated worse proliferative ability of SAA MSCs, and all studies demonstrated no difference in their surface marker expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among multiple studied factors, the dysfunction of BM environment and mesenchymal stromal cell dysregulation might contribute to the damage in the stem-cell niche (9). Immune pressure from T-cell-mediated mechanisms leads to somatic gene alterations in HSCs, resulting in immune evasion (10).…”
Section: Pathophysiology and Clonal Evolutionmentioning
confidence: 99%
“…Haploidentical HCT with CD45RA (4 patients), TCRab-CD19 depletion or PTCy (5 patients) was evaluated in 11 patients with SAA or MDS-refractory cytopenia of childhood (212). The conditioning regimens were heterogenous and consisted of Flu combined with irradiation techniques (9), Cy (9), busulfan, treosulfan, or thiotepa. Despite engraftment, 2 patients died, and 4 of 9 long-term survivors developed cGVHD.…”
Section: Haploidentical Hctmentioning
confidence: 99%
“…Mostly, Aplastic anemia (AA) patients have pancytopenia, with decreased levels of platelets and white blood cells 1 , 2 . The immune function of AA patients is always low, which makes AA patients susceptible to infection, and infection is also a significant cause of death in AA patients 3 , 4 . Infection, especially early pulmonary infection, has always been a fundamental problem for hematologists, mainly because pulmonary infection, especially early infection, is not easy to diagnose.…”
Section: Introductionmentioning
confidence: 99%